Transcranial Alternating Current Stimulation (tACS) Mechanisms and Protocols - Tavakoli, Amir V.; Yun, Kyongsik (Frontiers in Cellular Neuroscience, 2017)
Perception, cognition and consciousness may be modulated as a function of oscillating neural activity. Ongoing neuronal activity is susceptible to the modulation of synaptic activity and membrane potentials. Because of this susceptibility, transcranial alternating current stimulation (tACS) may be used for neuroplastic interventions. The advantageous features of tACS include the biphasic and sinusoidal tACS current, the ability to entrain large neuronal populations, and subtle control over somatic effects. Through neuromodulation of phasic, neural activity, tACS presents a powerful tool for investigations of the neural correlates of cognition alongside other forms of transcranial electric stimulation (tES) and noninvasive brain stimulation (NIBS). The rapid pace of development in this area requires clarification of best practices. Here, we briefly introduce tACS and review the most compelling findings from the literature to provide a starting point for the use of tACS under research conditions.